Conceptualization of genotype-phenotype relationships and the assessment of risk in advertising of direct-to-consumer and preimplantation polygenic tests - Petino Zappala, María Alejandra; Ariza, Lucía; Lima, Natacha Salomé (BioSocieties, 2024)
Recent decades have seen the increase of genome-wide analyses performed in the general population to compute the risk for multifactorial conditions. Polygenic risk tests, already available to clients via the direct-To-consumer (DTC) market, recently expanded to preimplantation genetic assessment of embryos in the context of fertility treatments (Preimplantation Polygenic Genetic Testing or PGT-P). While both kinds of tests rely on the same methodologies and are fueled by the promise of health optimization, they propose different interventions. Here, we compare the advertising strategies for companies offering DTC or PGT-P. We show that each company presents genotype-phenotype relationships to accommodate the intervention they propose and the clients’ expectations. While DTC companies grant a greater role to the environment and to genotype-environment interaction on health, discourse on PGT-P neglects any such interaction and undermines environmental factors. In all cases analyzed, while it is recognized that risk is a group property, the estimate is presented as an individual trait, and sometimes confounded with health status. Moreover, all companies recognize the uncertainty of risk estimations but frame it as a result of the lack of detailed information, justifying the gathering of clients’ data, and fueling promises of the betterment of future population health through individual action.
Online veröffentlicht: 30. September 2023
Gesehen am 09.02.2024